OPTIMASI PROTOKOL EKSTRAKSI DNA Elaeidobius kamerunicus - Sri Wening; Agus Eko Prasetyo; Tjut Ahmad Perdana Rozziansha; Agus Susanto (Jurnal Penelitian Kelapa Sawit, 2016)
African pollination weevil (Elaeidobius kamerunicus Faust) has an important role in the productivity of Indonesian oil palm plantation. Up to now, there has not been a comprehensive biological study of the species at molecular level. The basic knowledge is very useful for exploitation of the weevil for effective oil palm fruit set development. This research aimed to obtain DNA extraction protocol of E. kamerunicus for DNA fingerprinting of the species. Results showed that using a DNA extraction kit,material disruption by using micro pestle resulted the highest quantity of DNA, while there were no significant differences of resulted DNA quantity among treatments using tissue lyser for material disruption. DNA extracted by using micro pestle or tissue lyser for material disruption is adequate for DNA fingerprinting using AFLP (Amplified Fragment Length Polymorphism) and sequencing techniques.